Kegiatan Penapisan Kadar Air Dan Minyak Kulit Pada Populasi Dewasa Di SMP Kalam Kudus Jakarta - Linda Yulianti W; Junius Kurniawan; Farell Christian Gunaidi; Tosya Putri Alifia; Andini Ghina Syarifah (Jurnal Kabar Masyarakat, 2024)
The skin, as the body's largest organ, can function as an important barrier against dangers from outside the body. Insufficient water and oil levels in the skin can cause dry skin conditions. This can be caused by various factors, including age, sun exposure, and accompanying chronic diseases. Dry skin tends to cause itching, thereby increasing the risk of scratching and injury. A good level of skin hydration will improve an individual's quality of life. This screening activity for the adult population at Kalam Kudus Middle School was attended by 127 participants with an average age of 39 years. The mean water and oil content in the left hand were 39.3% and 17.6%, respectively. Meanwhile, the average water and oil content in the right hand was 41.2% and 18.5%, respectively. Through this activity, participants are expected to increase awareness of the importance of maintaining body and skin moisture.